Building knowledge-based economies in Africa: A systematic review of policies and strategies - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
Compared to other regions of the world, Africa is lagging in its drive toward knowledgebased economies. This study systematically reviews the literature in order to highlight the policies and strategies with which African countries can accelerate their current drive towards building knowledge-based economies. These are discussed in terms of three pillars of the World Bank's knowledge economy framework. They are the indices for: (i) education and skilled population, (ii) information and communication technology and (iii) economic incentives and institutional regime.
Keywords: O10; O30; O38; O55; O57; 330; Knowledge economy; Development; Africa